^{2}= 5x + 2

^{2}- (5x+2) = 5x + 2- (5x+2)

^{2}- 5x - 2 = 0

3x + 1 = 0

3x = -1

x-2 = 0

3X^2 = 5X + 2 ?

Tutors, sign in to answer this question.

When using the zero factor property, you need to set each factor to zero and then solve for the variable.

Using your equation

3x^{2} = 5x + 2

You want to subtract (5x+2) from both sides of the equation in order that you have an equation equal to zero

3x^{2} - (5x+2) = 5x + 2- (5x+2)

3x^{2} - 5x - 2 = 0

Factor the polynomial

(3x + 1 )(x - 2) = 0

Now, set each factor equal to zero and solve for x

3x + 1 = 0

3x = -1

3x + 1 = 0

3x = -1

x = -1/3

x-2 = 0

x-2 = 0

x = 2

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.